Endometritis in gilts: Reproductive data, bacterial culture, histopathology, and infiltration of immune cells in the endometrium - Padet Tummaruk (2018)
The aim of the present study was to quantify the number of immune cells infiltrated in the endometrium of endometritis gilts. Based on gross morphology, a selected 28 genital organs of endometritis gilts were investigated. The gilts were classified according to the ovarian appearance into three groups, i. e. follicular, luteal, and ovarian quiescent phases. Historical data, reason for culling, histopathology, bacterial identification, and number and type of immune cells in different layers of the endometrium were examined. The gilts were culled at 336 ± 63 days of age at a body weight of 142 ± 20 kg. The culling reasons included abnormal vaginal discharge (n = 10), repeat breeding (n = 6), anestrus (n = 6), abortion (n = 4), and not pregnant (n = 2). Bacteria identified from pus exudates included Escherichia coli (33.3%), Staphylococcus sp. (17.5%), α-hemolytic Streptococcus sp. (14.3%), and β-hemolytic Streptococcus sp. (9.5%). Neutrophils were the most common immune cells in the epithelial and subepithelial tissue layers of the endometrium, while lymphocytes were the most common immune cells in the glandular layer. Neutrophils in the epithelial and subepithelial layers of the endometrium in the luteal phase were lower than in the follicular and ovarian quiescent phase. During the acute stage, neutrophils were the most common immune cells in the endometrium, while during the chronic stages, lymphocytes, plasma cells, and eosinophils were the dominant immune cells. In conclusion, the number and type of immune cells in the endometrium of the endometritis gilts varied according to both the reproductive cycles and the stage of endometritis. Neutrophils, lymphocytes, plasma cells, and eosinophils indicate stages and the severity of endometritis. © 2009 Springer-Verlag London Limited.